Analysis of the lack of student activity in learning and efforts to overcome it - Riab, Ahmad Dzulfikkar (Maliki Interdisciplinary Journal, 2025)
Student activity in the learning process is one indicator of the success of education in schools. However, based on observations conducted at MTs Islamiyah Pakis, it was found that most students still showed a low level of participation, especially in discussion and questioning activities in class. This problem can have an impact on less than optimal understanding of the material and weaken students’ critical thinking skills. This study aims to analyze the factors causing low student activity and find effective strategies to overcome it. The methods used are observation, interviews, and documentation. The results show that the main causes of student lack of activity are lack of self-confidence, fear of answering incorrectly, and a classroom environment that does not fully support active participation. Therefore, a more interactive and supportive learning approach is needed, such as the application of a cooperative learning model and increasing communication between teachers and students. With these steps, it is hoped that students can be more confident and active in learning.